Secular trends: 10 and 20-year comparisons of sexual maturation among students. http://dx.doi.org/10.5007/1980-0037.2012v14n6p680 - Rodrigo Mateus Farias; Sandra Marcela Mahecha Matsudo; Gerson Luis Moraes Ferrari; Victor Keihan Rodrigues Matsudo (Universidade Federal de Santa Catarina, 2012)
The objective of this study was to verify the secular trends of sexual maturation of students between 11 and 15 years old, during a period of 10 and 20 years. The sample was composed by 1,002 students aged between 11 and 15 years; 536 boys (12.6±1.3 years old) and 466 girls (12.5±1.2 years old) who took part in the Ilhabela Mixed-Longitudinal Project on Growth, Development, and Physical Fitness. The students' assessment period occurred in 1990/91 (initial), 2000/01 (10 years later), and 2009/10 (20 years later). Sexual maturation was analyzed according to the self-assessment method and age at menarche (month and year) was collected retrospectively. The statistical analysis used was: one-way ANOVA, and Tukey's post-hoc test. The level of significance was p<0.01. The onset of menarche in the initial analysis was at: 12.5±1.2 years old; in the 2000/01 group: 12.3±1.0 years old (Δ=-1.6%), and in the 2009/10 group: 12.2±1.0 years old (Δ=-2.4%). Although there was a tendency towards reduction in age at menarche along the periods investigated, differences were not significant. There were significant differences only in genitals (G4), and pubic hair (P3) in boys after 10 and 20 years. In the same period, it did not occur any significant difference in maturational stages for girls. In conclusion, there was no secular trend of secondary sexual characteristics in boys (genital and pubic hair) and girls (breast and pubic hair) and in age at menarche over 10 and 20 years.